Pengaruh Pemberdayaan Perempuan dan Faktor Sosial Demografi Terhadap Penggunaan Kontrasepsi Modern di Jawa Barat - Alhamuddin; Rabiatul Adwiyah; Dadang Suhenda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The using of contraception in women is closely related to decreased fertility. In the Internation al Conference on Population and Development (1995), it is expected that women will absorb more information about the using of contraception and participate in using it, as the status of women's empowerment increases. This study aims to determine the effect of women's empowerment and socio-demographic factors on the using of modern contraception in West Java in 2017. The data used are acquired from the Indonesian Demographic and Health Survey (IDHS) in 2017. The research method uses binary logistic regression methods. It is a statistical method that uses binary data, where binary data is data that has only two possible outcomes. Ie results (0) fail, (1) success. Binary logistic regression tries to see how the relationship of some predatory variables with binary variables that have the possibility of failure and success. In this study the variable use of the contraception tool for the fertility rate of women aged 14-45 years. There are nine social demographic variables and five women's empowerment variables that significantly influence the use of modern contraception. The socio-demographic variables that significantly influence are age, female education, work status, husband's education, number of live children, ideal number of children, wealth index, area of residence, and family planning visits.